康熙皇帝成才之教育模式研究 - 赵, 晶莹 (2022)
回顾历史，古今中外很少有天生之专才，所谓人才或专才，只不过是后天孜孜不倦努力所造就的。要强调的是，人类是需要学习才能成为有才能的人，即使千古一帝的康熙也不例外。当后人羡慕前人成就时，莫忘了其背后真正成功的原因，这些成功的模式，仔细分析，不容易办到，但却是成才之核心价值。 教育乃百年树人大计，教育的本质是塑造一个才德兼备的智者；然而本文的主轴却是探究才学之培养，即如何培育一位有成就之帝王。 一位帝王要成才，背后总有其根本的原因。要探讨康熙之成才模式，他幼年所获得的教育模式其实有着直接的影响。本文重点在于探究康熙在成长的路上所走过的路径，这一系列的经验经过梳理后，实际上可以成为后人借鉴之教育模式。 本论文共分为九章，内容涵盖所有导致康熙成才的教育模式，这一套模式是很有系统的、完整的模式，展现了康熙成功背后之面貌。 首先，要成为盛世之明君，背后需要有大格局之衬托，康熙身处皇帝世家，他的格局先天性已占优势，因此康熙囊括了属于皇帝世家所拥有之资源。在此情况下，康熙成才的机率自然会比普通老百姓来得高。第三及第四章论述康熙之成功，主要是与其个人内在动力有关键性之影响。忧患意识以及自制力皆是主导康熙向前迈进之最原始动力，这些动力鞭策康熙坚韧不拔地勇往直前，并成就其非凡之盛世。 根据历史，康熙追求学问的态度，非凡人所能及。身为皇帝，虽日理万机，仍手不释卷，孜孜于学习儒家经典，这是罕见之处，第五章深入探究康熙之治学态度，通过其学习态度，找出其让人推崇之处。第六章和第七章则指出无数人物悉心之指导，引领着康熙前进，这些人物包括先祖努尔哈赤、皇太极与顺治帝，祖母孝庄以及循循善诱的导师；而康熙从小阅读的古代经典，对他的影响深远，因为汉族经典的精神启发与熏陶其内心，成就其伟大的人格；而传统的狩猎精神，亦锻炼其强健的体魄，让康熙有能力在战场上驰骋以及处理国政。这一系列之模式，让康熙思想上与身体上皆茁壮成长。 第八章是论述概率论。黑天鹅理论要旨强调康熙之防微杜渐以及吸收皇族家族里的各项资源，以便成为知识渊博及能力强大的君主。本段落也描述对于教育的实际真相，即教育本身是必需经过长年累月的学习才能看到效果，短时期是无法成为强大之君主，这是特别需注意的。 结论即强调透过一系列之教育模式，做出统合之结局，来印证康熙的成功不是偶然的。这一套成才模式实际上是一套可借鉴之模式，其核心价值在于栽培像康熙一样出类拔萃之领导者。本文所探讨之成才教育模式，是可以一代接一代传下去之模式，因为它有其规则性可以仿效。执行得越符合这一套模式，那么成才之机率就越高，康熙最终可以成为有成就之帝王，源自于此。According to history, geniuses are not born. They are made. Outstanding individuals are often the result of hard work and studying. Emperor Kangxi is a perfect example. We will try to study the real reasons behind his success as these reasons are the key values to greatness. Education is the only way to shape an individual’s character talent and moral values. The main subject of this thesis is to study the cultivation of talent and the making of a successful emperor. There is always a fundamental reason behind an emperor's success. To discuss Kangxi's talent model, it has a direct relationship with the education model he obtained in his childhood. The focus of this article is to explore the path Kangxi has taken on the road to growth. After sorting out his experiences, it can become an education model for future generations to follow. This thesis is divided into nine chapters. All the chapters cover all the educational models that led to the success of Kangxi. This set of models is very systematic, complete and shows the true reasons behind Kangxi's success. First，the environment creates a person's status. To become a successful emperor in a prosperous age, it is necessary to have a suitable strategic environment behind it. Kangxi was born in an emperor's family. His environment is inherently dominant, so Kangxi has the resources belonging to the emperor's family. In this case, the probability of Kangxi becoming a successful emperor will naturally be higher than that of ordinary peasants. Third and fourth chapter describes Kangxi's success is mainly due to the key influence on his personal inner motivation. Insecurity and impulse control are the most primitive powers that led Kangxi to move forward. These powers urged Kangxi to persevere and to achieve his extraordinary prosperity. According to history, Kangxi's pursuit of learning is beyond the reach of normal people. As an emperor, although he is well-versed in everything, he still reads frequently, and is diligent in studying Confucian classics. This is a rare thing. The fifth chapter delves into Kangxi's attitude of diligence, and elaborates on his learning attitude to find out why he is admired by all. In fact, sixth and seventh chapter describes countless characters have guided Kangxi's advancement with care. These characters include the ancestors Nurhachi, Emperor Taiji and Shunzhi Emperor, grandmother Xiaozhuang and other knowledgeable mentors ; The ancient classics had a profound influence on him, because the spirit of the Han classics inspired and nurtured his heart and achieved his great personality. The traditional hunting spirit has also strengthened Kangxi’s physical abilities, giving Kangxi the ability to gallop on the battlefield and handle political affairs. This series of models allowed Kangxi to thrive both mentally and physically. Chapter eight is regarding probability theory. The black swan theory is to emphasize Kangxi's defense against the dangers and absorb the resources of the royal family in order to become a knowledgeable and powerful monarch. This thesis also describes the actual truth about education, that is, education itself must be studied over many years to see the effect, and it is impossible to become a powerful monarch in a short period of time. This is particularly noteworthy. This thesis emphasizes that through a series of education models, a unified ending is made to prove that Kangxi's success is not accidental. This set of talented models is actually a set that is use for reference. Its core value is to cultivate leaders like Kangxi. The talent education model discussed in this article is a model that can be passed down from generation to generation, because it has its regularity to be followed. The more our actions conform to this education model, the higher the chance of success, and Kangxi can eventually become an accomplished emperor.